Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.24200/sci.2018.50153.1567
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of shallow foundations rested on saturated loose sand by zeolite-cement mixture: a laboratory study

Abstract: Improvement operation of sands is carried out frequently by cement together with several other additives. Common additives have high manufacturing cost and negative environmental impact during their manufacturing process and recycling in nature. Zeolite as a mineral substance for cement replacement can improve the strength parameter of a treated sand, without the negative de ciencies of the common additives. In this study, Uncon ned Compression Strength (UCS) and small-scale 1g model tests were conducted to ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
(24 reference statements)
0
5
0
Order By: Relevance
“…Canpolat et al [25] reported that the replacement of 20% cement with zeolite enhanced the strength of the cement paste. Moreover, MolaAbasi et al [26] and Salamatpoor et al [27] expressed that the UCS of the cemented sand increases when the cement is replaced by zeolite at an optimum proportion of 30 and 40%, respectively. It can be concluded that by the cement substitution with 30% zeolite, the presence of Ca(OH) 2 as a product of hydration reaction comes into a balance with the silica and alumina available in zeolite enrolling in the pozzolanic reaction, and all these chemical constituents are entirely consumed to yield CSH and CAH gels, resulting in the maximum CBR.…”
Section: Results Of Cbr Testsmentioning
confidence: 99%
“…Canpolat et al [25] reported that the replacement of 20% cement with zeolite enhanced the strength of the cement paste. Moreover, MolaAbasi et al [26] and Salamatpoor et al [27] expressed that the UCS of the cemented sand increases when the cement is replaced by zeolite at an optimum proportion of 30 and 40%, respectively. It can be concluded that by the cement substitution with 30% zeolite, the presence of Ca(OH) 2 as a product of hydration reaction comes into a balance with the silica and alumina available in zeolite enrolling in the pozzolanic reaction, and all these chemical constituents are entirely consumed to yield CSH and CAH gels, resulting in the maximum CBR.…”
Section: Results Of Cbr Testsmentioning
confidence: 99%
“…Concerning the study by Salamatpoor et al [24], the experimental study involved three dominant equipment, including a frame, a transparent tank (as a rigid box), and measuring instruments. The frame is composed of IPE 18, which is screwed to a rigid foundation with eight M24 bolts.…”
Section: Small-scale 1 G Model Testmentioning
confidence: 99%
“…Since the inside width of the box was equal to the length of the model foundations, a plain-strain condition was generally maintained [15]. Before conducting the tests, for each test, some preliminary works were required for higher precision, such as calibrating the load cell, dialing gauge, and depleting the piezometer tubes from the air.…”
Section: Test Facilities Instrumentation and Model Preparationmentioning
confidence: 99%
“…As the width and the length of the testing tank were constant, the relative density was controlled by measuring the height (or volume) and also the weight of each layer. It was considered to reconstitute the model sand deposit at a relative density (D r ) of 302% through a water sedimentation process [15].…”
Section: Test Facilities Instrumentation and Model Preparationmentioning
confidence: 99%